Factors Associated With Heel Pain in Young Professional - Iram Nawaz, Amna Bukhari, Warda Shafique, Quratulain, Ume Aiman, Umer Rafique, S. Jabeen, Faiza, Sania Maqbool, Hira Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Heel pain is a common condition that affects people with all age groups but mostly it is found in young and middle age groups. Different factors are thought to be associated with heel pain such as age, body mass index, height , weight, %age of sitting and standing during most part of the day. Aim: To identify the factors associated with heel pain and to measure the frequency of heel pain in young professionals. Methodology: It was an Observational cross sectional study design which was conducted in the different office and hospital setting of Lahore. 266 participants were taken after meeting inclusion criteria. Data was collected using a standardized questionnaire. SPSS version 26 was used for data analysis. Results: there were 266 participants in current study of which 166(62.4%) reported heel pain. Heel pain was reported majorly be females (77.8%). Among young professionals, heel pain was found to be maximum among the lecturers/Teachers (42.2%), nurses (21.7%), doctors and Physiotherapist (6%) and office workers (24.1%). 44.6% participants found effect of heel pain on their quality of work to some extent and 30.1% have strong impact on their QOW. Conclusions: From above results its concluded that heel pain is common among young professionals including lecturers, nurses, teachers and physiotherapist. The main factors associated with heel pain was age , gender , percentage of standing and sitting , job nature are associated with heel pain. The factor that can be modified for decreased incidence of heel pain is percentage of standing and if prolonged standing is required according to job nature then it is suggested to change their pressure on heels i.e. by incorporating some walk or sitting interval between hours of continuous weight bearing on feet. Keywords: young professional, heel pain , BMI, planter fasciitis, Long working hours, nature of job